2017
DOI: 10.6002/ect.2016.0069
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Objectives: Urinary tract infection is the most common type of bacterial infection in kidney transplant procedures, with adverse effects on graft and patient survival. We aimed to evaluate the risk factors of recurrent urinary tract infection in renal transplant recipients and its impact on patient and graft survival. Materials and Methods: In a cohort of 1019 patients who were transplanted between 2000 and 2010 at Hamed Al-Essa Organ Transplant Center in Kuwait, 86% developed at least 1 episode of urinary tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Urinary tract infection was defined by leukocyturia (dipstick positive and/or 5–10 leukocytes/microscopic field in a urinary sediment) in combination with a urine culture with >10 4 bacterial colonies, with or without clinical symptoms. 18 Viral infections (hepatitis B/C, BK virus, and cytomegalovirus) were determined by locally available nucleic acid tests, preformed antibodies by the lymphocytotoxic panel reactive antibody test. Delayed graft function was defined as <500 mL urine within 24 h posttransplantation and/or need of dialysis within the first week (excluding cases with dialysis solely because of hyperkaliemia).…”
Section: Methodsmentioning
confidence: 99%
“…Urinary tract infection was defined by leukocyturia (dipstick positive and/or 5–10 leukocytes/microscopic field in a urinary sediment) in combination with a urine culture with >10 4 bacterial colonies, with or without clinical symptoms. 18 Viral infections (hepatitis B/C, BK virus, and cytomegalovirus) were determined by locally available nucleic acid tests, preformed antibodies by the lymphocytotoxic panel reactive antibody test. Delayed graft function was defined as <500 mL urine within 24 h posttransplantation and/or need of dialysis within the first week (excluding cases with dialysis solely because of hyperkaliemia).…”
Section: Methodsmentioning
confidence: 99%
“…Another study concluded that combining dipsticks leucocyte and nitrite tests has a sensitivity and specificity of 82% and 84%, respectively (Tawab et al, 2017). A different study from Tanzania reported 56% and 85% sensitivity and specificity, respectively (Katunzi et al, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Kidney transplant recipients are particularly vulnerable to UTI due to certain factors that are uniquely associated with transplantation. These include immunosuppressive therapy to prevent rejection, urologic instrumentation including stents, impaired urogenital physiology consequent on surgical alteration of the urogenital system, native kidney diseases such as polycystic kidney disease, reflux nephropathy, nephrolithiasis, and neurogenic bladder (Tawab et al, 2017;Fiorentino et al, 2019). The incidence of recurrent UTI is exceptionally high among kidney transplant recipients and has led to the emergence of multidrugresistant organisms with high hospitalisations costs (Al Midani et al, 2018;Rodríguez Sánchez et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations